Sir Richard Owen’s fly, Gyrostigma rhinocerontis (Diptera: Oestridae): correction of the authorship and date, with a list of animal names newly proposed by Owen in his little-known 1830 catalogue - Evenhuis, Neal L. (Zootaxa, 2012)
The authorship and date of publication of Oestrus rhinocerontis is corrected from the Rev. F.W. Hope in 1840 to SirRichard Owen in 1830. A list of new names proposed in Owen (1830) is given, many of which are earlier than publishedelsewhere and have been missed by previous workers. Additionally, the name Gyrostigma rhinocerontis bicornis Brauer is shown to be an available name dating from Brauer (1896).